Room temperature ferromagnetism in Ti0.985Co0.015O2-δ thin films grown by pulsed laser deposition technique - Mohanty P.; Ganesan V.; Rath C. (My University, 2025)
Ti0.985Co0.015O2-δ thin films are deposited at 0, 0.1, 1 and 300 mTorr oxygen partial pressures by pulsed laser deposition (PLD) technique. Glancing angle x- ray diffraction (GAXRD) and micro-Raman spectroscopy show that the phase changes from rutile to anatase with increasing oxygen partial pressure. From Rutherford backscattering spectroscopic (RBS) technique, O to (Ti+Co) atomic ratio is found to increase with increasing oxygen partial pressure. Further, the simulation of RBS data while reveals non-uniform distribution of Co throughout the film deposited at 0 and 0.1 mTorr oxygen partial pressures, at 1 and 300 mTorr oxygen partial pressure, Co distribution is found to be uniform. Magnetic measurements confirm the room temperature ferromagnetism (RTFM) in all the films independent of the phase. Magnetic force microscopy (MFM) further supports the ferromagnetic nature of the films. We attribute the ferromagnetism in the films to be arisen from defects like oxygen vacancies rather than any contamination or Co clustering. © (2013) Trans Tech Publications, Switzerland.